Faktor yang Berhubungan dengan Status Gizi Balita di Wilayah Kerja Puskesmas Cawas II Klaten - Awanis, Almas; Ariyanti, Lilik (FORIKES, 2023)
Many factors can affect the nutritional status of children under five, both direct factors, indirect factors and remote factors. So research is needed that aims to find out what factors are related to the nutritional status of toddlers in the Work Area of the Cawas II Health Center in Klaten. This study applied a cross-sectional design. The respondents of this study were 189 toddlers in the working area of the Cawas II Health Center in Klaten who were selected by purposive sampling technique. Data was obtained through filling out a questionnaire which was filled in directly by the respondents. Data was presented descriptively, then analyzed using the Chi-square test. The results of the analysis showed that the p-value for each factor was: education = 0.852, mother's occupation = 0.016, history of exclusive breastfeeding = 0.011 and income = 0.77. It could be concluded that the factors associated with the nutritional status of toddlers in the working area of the Cawas II Klaten Health Center were a history of exclusive breastfeeding and mother's work.Keywords: toddler; nutritional status; Exclusive breastfeeding; mother's occupation ABSTRAK Banyak faktor yang bisa mempengaruhi status gizi balita, baik faktor langsung, faktor tak langsung maupun faktor jauh. Maka diperlukan penelitian yang bertujuan untuk mengetahui faktor apa saja yang berhubungan dengan status gizi balita di Wilayah Kerja Puskesmas Cawas II Klaten. Penelitian ini menerapkan rancangan cross-sectional. Responden penelitian ini adalah 189 balita di wilayah kerja Puskesmas Cawas II Klaten yang dipilih dengan teknik purposive sampling. Data diperoleh melalui pengisian kuesioner yang diisi secara langsung oleh responden. Data disajikan secara deskriptif, selanjutnya dianalisis menggunakan uji Chi-square. Hasil analisis menunjukkan bahwa nilai p untuk masing-masing faktor adalah: pendidikan = 0,852, pekerjaan ibu = 0,016, riwayat ASI eksklusif = 0,011 dan pendapatan = 0,77. Dapat simpulkan bahwa faktor yang berhubungan dengan status gizi balita di wilayah kerja Puskesmas Cawas II Klaten adalah riwayat ASI eksklusif dan pekerjaan ibu.Kata kunci: balita; status gizi; ASI eksklusif; pekerjaan ibu